Failure mechanism of PEM fuel cell under high back pressures operation. (21st May 2019) - Cai, Chao; Rao, Yan; Zhang, Yu; Wu, Fan; Li, Shang; Pan, Mu
Abstract: Proton exchange membrane fuel cells (PEMFCs) are expected to function under relatively higher back pressures for targeting higher outpower. Under this condition, the durability of fuel cells will be a huge challenge for commercialization. In our study, a 1000-h durability experiment was performed on a PEMFC to investigate the durability under high back pressures. A semi-empirical fuel cell polarization curve model was used to separate the activation and concentration losses, and study their changes with testing time at different current densities. In addition, the charge transfer resistance (Rct ) related to oxygen reduction reaction (ORR) in the catalyst layer was also investigated. Additionally, the mass transfer resistance (Zd ) was investigated using electrochemical impedance spectroscopy (EIS). Moreover, the contact angle and energy-dispersive X-ray spectrum (EDX) of carbon paper surface were characterized. The results indicated that the increase in mass transfer resistance was the biggest contributor to the loss of cell voltage with testing time. The decrease in contact angle of carbon paper surface implied that the weakening of hydrophobicity contributed to an increase in the mass transfer resistance, which comes from the PTFE loss observed from EDX. This may result from the aggravated corrosion of carbon fiber or physical erosion induced by flooding in fuel cell under high back-pressure. Highlights: A durability test of 1000 h was achieved under a high back pressure of 250 kPa. The degradation reasons of PEMFC were analyzed using polarization curve fitting. Decrease in GDL water management led to performance degradation. Corrosion of carbon and PTFE loss were accelerated under high back pressure.